8(9x-2)=72x-2

Simple and best practice solution for 8(9x-2)=72x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(9x-2)=72x-2 equation:


Simplifying
8(9x + -2) = 72x + -2

Reorder the terms:
8(-2 + 9x) = 72x + -2
(-2 * 8 + 9x * 8) = 72x + -2
(-16 + 72x) = 72x + -2

Reorder the terms:
-16 + 72x = -2 + 72x

Add '-72x' to each side of the equation.
-16 + 72x + -72x = -2 + 72x + -72x

Combine like terms: 72x + -72x = 0
-16 + 0 = -2 + 72x + -72x
-16 = -2 + 72x + -72x

Combine like terms: 72x + -72x = 0
-16 = -2 + 0
-16 = -2

Solving
-16 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 18+10=-4(2x-7) | | 5x-21=x+31 | | 39=8x-(2x-3) | | 18-4e=e+3 | | 5r-(2r+18)=16 | | -2(2+3x)=-28+6x | | -2a+7-3(-9-4a)= | | -17-2x=9+t | | 7x=--6 | | -.6a=2 | | r+12= | | dfghj=k | | 7n+6n+-5=4n+4 | | 4+2m=6+2m | | 4d+2(7+-2)= | | -1.6=x+1.1 | | 5x-2-x=30 | | c-33+2=443 | | 5-3=43 | | 6z-19-z+4=0 | | 4x+2x+3=9 | | (-4x^2+3x-1)-(4x+2)= | | 4.3=b-1 | | -8+5x-7x=-16 | | 5.16-p=15.48 | | 12-2c+6c= | | 12-22x= | | 0.75(-6)-6= | | 4r-r= | | 3x+9=44-3x | | 29+n=-(-5n-5) | | 7(2+w)=6(w-9) |

Equations solver categories